THE ROLE OF FICTION LITERATURE IN SHAPING CHILDREN’S SPIRITUAL, MORAL, AND EMOTIONAL DEVELOPMENT (Web of Teachers: Inderscience Research, 2026)
This article explores the role of fiction literature in shaping children’s spiritual, moral, and emotional development from an interdisciplinary pedagogical perspective. Fiction literature is analyzed as a powerful educational medium that influences children’s value systems, emotional intelligence, ethical reasoning, and aesthetic awareness. The study applies qualitative research methods, including theoretical analysis, observation, and comparative interpretation, to examine how literary texts affect children’s personal growth. The findings demonstrate that fiction literature significantly contributes to moral formation, empathy development, language enrichment, and cultural identity. The article emphasizes the necessity of systematically integrating fiction literature into educational practices to foster spiritually mature and socially responsible individuals.